Haemato-biochemical study of free ranging gaur - A B SHRIVASTAV; K P SINGH; P NIGAM; K SANKAR; H R JOSHI; N RAJPUT; A ROKDE; B NAVANITHAN; S AGRAWAL; J S CHAUHAN (Indian Journal of Animal Sciences, 2014)
To support the health monitoring and care for the endangered gaur species, 18 apparently healthy, free-ranging gaurs (Bos gaurus gaurus) of either sex were immobilized with etorphine HCl and azaperone. The haematological values, viz. total erythrocyte count, haemoglobin, packed cell volume, erythrocyte sedimentation rate, mean corpuscular volume, mean corpuscular haemoglobin, mean cell haemoglobin concentration, total leukocyte count, neutrophils, lymphocytes, monocytes, eosinophils, and basophiles, were encountered. The principal biochemical constituents of blood serum were revealed as glucose, phosphorus, calcium, chloride, cholesterol, total proteins, albumin, creatinine, uric acid, blood urea nitrogen, total bilirubin, alanine aminotransferase, aspartate aminotransferase, and alkalinephosphatase. There was a significant difference with the advancing age in meanÂ  corpuscular volume, neutrophil, eosinophil, cholesterol and alanine aminotransferase levels.